Harmonization of Javanese Customs and Islamic Traditions in Clean Village - Mudijono, Mudijono; Halimahturrafiah, Nur; Muslikah, Muslikah; Mutathahirin, Mutathahirin (INJIES: Journal of Islamic Education Studies, 2025)
This tradition is not merely a customary ceremony but a philosophical representation of the Javanese worldview in understanding the relationship between humans, nature, fellow beings, and the Divine. This study examines the dynamics of interaction between Javanese customs and Islam in the Clean Village tradition as a complex cultural phenomenon. The research aims to explore adaptation mechanisms, transformation, and preservation of tradition in the context of contemporary social changes. Using library research method with qualitative-interpretative approach, the study analyzes cultural, ethnographic, and religious literature sources. Research findings reveal Clean Village as a dynamic cultural construction continuously evolving through symbolic negotiation between locality and universality. Modernization, demographic changes, and religious dynamics influence tradition transformation. Constructive preservation model emphasizes participatory approaches, cross-generational cultural education, and interpretative creativity spaces. Research implications include responsive cultural heritage preservation strategies that maintain spiritual and cultural essence while adapting to social changes.